Foreign Direct Investments in Poland After 2000 - Jacek Piszewski (Contemporary Economics)
The more of the world economy globalize and the role of FDI increases. FDI have impact on development of regions and they decrease the differences between them. Although the number of FDI in Poland increases rapidly, the total value of them do not have enough influence on Polish economy growth. Considering the number of FDI, from early 90ís Poland has been a leader among other countries of Middle-East Europe. The main factor of the FDI flow was the transformation of economy system, what established law, economic and infrastructure condition. Membership in the OECD (1996) helped Poland in setting up all the procedures and law system optimal for foreign investors. The attractiveness of Poland increased under the influence of becoming a member of the NATO (1999) and the EU (2004).